1663 Use, misuse, abuse of pesticide use in agriculture. which interventions are needed to promote safety and health of workers?. (24th April 2018) - Colosio, Claudio; Laan, Gert van der; Mandic-Rajicevic, Stefan
Abstract : Aim of special session: Pesticides are necessary in the modern agriculture and their use is unavoidable. However, very often misuse and abuse bring about unacceptable risk to agricultural workers and the environment. How to promote a safe us of these compounds? Worldwide known field experts will discuss this topic. Since it wil be a round table with an open discussion among speakers and of speakers with public, no title of presentation has been asked to the persons invited to contribute Claudio Colosio 1, Gert van der Laan 2, Stefan Mandic-Rajicevic 1, Erik Jors 3, Andrea Rother 4, Susan Brumby 5, Shengli Niu 6 1 Department of Health Sciences of the University of Milan and International Centre for Rural Health of the S. Paolo Hospital, Italy 2 Foundation Learning and Developing Occupational Health, PE Leusden, Netherlands 3 Department of Occupational and Environmental Medicine, Odense University Hospital, Odense, Denmark 4 Division of Environmental Health, School of Public Health and Family Medicine, University of Cape Town, Cape Town, South Africa 5 National Centre for Farmer Health, Western District Health Service, Hamilton VIC Australia 6 International Labour Organisation, Geneva, Switzerland